Can bowl-like B30 nanostructure sense toxic cyanogen gas in air?: a theoretical study. (2nd September 2018) - Rahimi, Rezvan; Solimannejad, Mohammad
ABSTRACT: In this work, an attempt has been made to study sensing performance of bowl-like B30 nanostructure towards toxic cyanogen gas using density functional theory (DFT) at B97D/6-31+G(d) computational level. The results reveal that B30 nanostructure is a proper sensor for sensing of toxic cyanogen gas. The most favourite adsorption site of B30 is the exterior boron atoms that lead to the adsorption energy of −78.48 (kJ/mol) with the remarkable change in electronic properties of B30 . The competitive sensing of cyanogen gas in the presence of water, oxygen and nitrogen molecules is also considered. Significant changes in the electronic properties of B30 due to adsorption of cyanogen in presence of O2, H2 O and N2 gases enable it to be used in the detection of toxic cyanogen gas in air. GRAPHICAL ABSTRACT: